2021
DOI: 10.1111/cpr.12986
|View full text |Cite
|
Sign up to set email alerts
|

NLRX1/FUNDC1/NIPSNAP1‐2 axis regulates mitophagy and alleviates intestinal ischaemia/reperfusion injury

Abstract: Ischaemic reperfusion (IR) injury is characterized as the damage caused to the tissues due to the return of blood supply (reperfusion) after a brief duration of lack of oxygen (ischaemia). Affecting a wide range of population and organs, they are usually observed as a consequence to conditions such as trauma, shock, strangulation, mesenteric artery thrombosis and intestinal obstruction. 1-4 Ischaemia by itself damages the cells, which is further exacerbated by the restoration of blood flow resulting in increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…Interestingly, Wang et al ( Wang et al, 2021 ) proposed that FUNDC1 was an integral mitochondrial outer-membrane protein that could increase the expression of VEGF and promote endothelial cell angiogenesis. Similarly, FUNDC1 not only alleviates ischemia–reperfusion injury but also inhibits apoptosis ( Wang et al, 2018 ; Jiang X. et al, 2021 ; Cai et al, 2021 ; Li et al, 2021 ). In our study, we observed that MLT treatment reduced the area of ischemic necrosis of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wang et al ( Wang et al, 2021 ) proposed that FUNDC1 was an integral mitochondrial outer-membrane protein that could increase the expression of VEGF and promote endothelial cell angiogenesis. Similarly, FUNDC1 not only alleviates ischemia–reperfusion injury but also inhibits apoptosis ( Wang et al, 2018 ; Jiang X. et al, 2021 ; Cai et al, 2021 ; Li et al, 2021 ). In our study, we observed that MLT treatment reduced the area of ischemic necrosis of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…Among the top 50 significant DEGs ( Table 1 ), several genes, such as ERBB3 , RCAN1 , and NLRX1 were previously reported to be related with ICM [ 32 , 33 , 34 , 35 , 36 ]. ERRB3 , erb-b2 receptor tyrosine kinase 3, has been reported as a protective factor which inhibits death mechanisms activated by redox stress and supports an involvement of this receptor in the pro-survival responses after MI/R injury [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cardiomyocytes depleted of RCAN1 were more sensitive to simulated MI/R and the calcineurin/Rcan1-signaling cascade could act as a potential therapeutic target through which to benefit from innate circadian changes in cardiac protection without disrupting core circadian oscillations that are essential to cardiovascular, metabolic, and mental health [ 34 ]. NLRX1 , NOD-like receptors family member X1, is significantly downregulated following intestinal MI/R injury [ 35 ], and ablation of the mitochondrial NLRX1 exerts a detrimental effect on acute cardiac infarction induced by a prolonged ischemia-reperfusion episode and activates potential MI/R injury mechanisms contributing to increased MI/R injury, related to elevated energy metabolism and diminished Akt [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…FUNDC1-related mitochondrial dysfunction contributes to various pathophysiological processes, such as heart diseases, intestinal ischemia/reperfusion injury, and metabolic disorders. FUNDC1 is generally considered to be protective in these diseases because FUNDC1-mediated mitophagy can alleviate the damage caused by intracellular stress such as hypoxia and thus benefit overall outcomes [79][80][81]. FUNDC1 is also localized in mitochondrial-associated endoplasmic reticulum membranes (MAMs) and plays a significant role in the communication between the ER and mitochondria in the heart and sustains normal cardiac function [82].…”
Section: Fundc1 Signaling Pathway In Mitophagymentioning
confidence: 99%